NILAI-NILAI KARAKTER DALAM PEMBELAJARAN BAHASA ARAB - Erni Zuliana (Institut Agama Islam Negeri (IAIN) Metro, 2017)
One of the fundamental problems underlying the author's take on this study, because the learning Arabic has given a teacher of Arabic language still tend to use examples of vocabulary which has not yet led to the formation of the positive character of the child. So the writers try to unearth about the facts associated with the learning process that is in the Madrasah Aliyah Negeri (MAN) I Sragen. As a manifestation of the cultivation of character values ​​in Arabic learning, by formulating a problem formulation is; How do teachers implement the Arabic character values in Arabic learning at MAN I Sragen. The subject of this research is the students of class XI MAN I Sragen about 303 students. The discussion in this research was qualitative in nature. Data collection methods used in this research are; observation, interviews, and documentation. The results of this research show that implementation of the cultivation of the values of the characters in the Arabic language learning in MAN I Sragen implemented with a wide variety of ways from either intrakurikuler or extracurricular activities. As for the activities of intrakurikuler are integrated into subjects such as in teaching and learning activities (KBM), an extracurricular activities conducted outside the hours of instruction and implementation of character education through orientation learning Arabic in schools that teachers do more accentuated on the example, conditioning and developing learner behavior that reflects the attitude of the confident, Independent, Communicative, Creative, Responsible, Curiosty, like to read.